"Souvenir Shopping is for Schmucks!": Exploring Tourists' Deviant Behavior Through the Items They Bring Back. (February 2023) - Harris, Lloyd C.; Magrizos, Solon
Tourist misbehavior is well documented in the literature and has predominantly focused on the visible, major, or felonious forms of deviance, such as vandalism, violence, or theft. We argue for the importance of considering a more subtle side of tourist misbehavior often tolerated, ignored, or even enabled by host communities and hospitality employees. Exploring the more subtle side of tourist misbehavior is important, because it is more clandestine and less extreme than obvious misbehaviors, yet its prevalence suggests important business and environmental implications. We undertook in-depth interviews with 47 frequent travelers and employed a criminological lens, that of deviant leisure, to uncover a range of deviant tourist behaviors by focusing on the accumulation of traveling mementos (items that tourists bring back from their travels). Two dimensions of memento accumulation emerged with eight forms of tourist misbehavior, each with unique motives, practices, and implications. Findings point to the importance and mass appeal of these more subtle and elusive deviant practices. Suggestions for practitioners, policy makers, and academics are then discussed.